The quality systems of additive technologies for aerospace parts manufacturing - Kokareva, Victoria; Smelov, Vitaliy; Zvyagincev, Maksim (Nexo Revista Científica, 2023)
In this study, the quality system for Ti-6Al-4V alloy manufacturing by selective laser melting was analyzed by using the Grey relation analysis and additive manufacturing quality methodology. In proposed methodology, the multicriteria problem is solved by selecting an optimal alternative AM technological process parameters combinations to meet the required quality parameters (desired goals) of the aerospace parts according several criteria. Decision algorithm for planning additive manufacturing was developed for building alternatives matrix and the adaptation coefficient evaluating. As quality criteria in model were chosen accuracy, roughness, strength, cost, printing time. Based on the analysis of the values of the adaptation coefficients for SLM, DMD and EBM technologies, the first type of technology for the manufacture of aerospace product, selective laser melting, is accepted as optimal.